Analisis Keberlanjutan Perkebunan Sawit Rakyat dalam Mendukung Indonesian Sustainable Palm Oil di Kecamatan Tungkal Ilir Kabupaten Banyuasin - Rizka Nurjanah; Herry Wirianata; Fariha Wilisiani; Juni Mulya Pratama (Jurnal Agro Industri Perkebunan)
Indonesia's palm oil industry has long faced criticism and denial, accusations that the palm oil industry is unsustainable, and smallholder plantations are seen as contributing to environmental risks. In response to this, the Indonesian government, to ensure the sustainability of the palm oil industry, created a sustainability standard called ISPO, which is mandated to be mandatory for all companies and smallholders through presidential regulation number 44/2020 with a grace period of 5 years to fulfill these obligations. However, these efforts faced various problems, especially for independent smallholders. Based on the problems faced, this study aims to determine the realization of ISPO principles and criteria and identify the achievement of ISPO principles and criteria in smallholder oil palm plantations in Tungkal Ilir District, Banyuasin Regency. The research method used is a quantitative descriptive approach with Guttman scale measurements to analyze the realization of the application of ISPO principles and criteria and identify the achievements of ISPO principles and criteria. From many study results, the realization of the implementation of ISPO principles and criteria in Tungkal Ilir District from the available indicators has yet to be met, and many still need to.  Many require more attention, including the criteria for legality and management of smallholders, criteria for obligations related to environmental permits, technical criteria for applying oil palm cultivation and transportation, and the principle of implementing transparency.